SOSIALISASI KONSEP GREEN RUANG TERBUKA HIJAU (RTH) PADA TAMAN KOTA DI KECAMATAN JATIASIH KOTA BEKASI - Kumba Digdowiseiso; Ria Ria (LPPM Universitas Bina Bangsa, 2023)
City Parks around the Jatiasih Jakarta Outer Ring Road (JORR) Toll Road, Bekasi City, have great potential to be developed in supporting recreational and sports activities and activities for the community if the existing programs at the regional government in particular can be followed up jointly. by local government, administrators, communities, and universities. Management and community awareness of the importance of maintaining the cleanliness and safety of City Parks around the Jatiasih Jakarta Outer Ring Road (JORR) Toll Road, Bekasi City needs to be carried out because management and community participation are considered low. Therefore, it is necessary to increase the understanding of the Green Open Space (RTH) concept for managers and the surrounding community so that the cleanliness of City Parks around the Jakarta Outer Ring Road (JORR) Jatiasig Bekasi City Toll Road can be enjoyed by all parties